FENOMENA BERBAGAI SIFAT FISIKA DAN KIMIA TANAH MENDUKUNG KETAHANAN TANAMAN PANGAN DI SUMATERA BARAT - Jamilah Munir; Welly Herman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The objective was to examine the phenomenon of physical and chemical properties of soil which is used as a center of agricultural cultivation in supporting food security in West Sumatra. The experiment was conducted by survey to various locations by taking composite soil samples in the field. Some types of soil taken include Histosol from Anai Padang Pariaman; Ultsiol from Lubuk Minturun; Inceptisol from Limau Manis and Siteba city of Padang; Andisol from Danau Kembar and Lembah gumanti Kab. Solok.  The result was can be concluded that Ultisol Lubuk Minturun more potency for  tropical fruits. Andisol in Lembah Gumanti and Danau Kembar Kab. Solok has decreased its chemical quality. It is necessary to increase soil pH to be suitable for the development of vegetable crops and food crops. The use of lime and organic matter in a proper fertilizing package can reduce the use of heavy fertilizer for vegetable crops and horticultura. Histosol utilization for wetland rice cultivation needs to be careful because the acidic pH and the number of organic acids are toxic. Inceptisol Limau Manis Padang has a neutral pH, and is very good for developing food cultivation in support of food security in West Sumatra.